Estudo da variação da resistência ao puncionamento estático de geossintéticos em contato com efluente agressivo. - Peixoto, Rafaelly Beserra (2023)
Geosynthetics are synthetic materials that can be used in various environmental protection and environmental damage remediation applications. Such are the cases of waste confinement, contaminated land confinement and land decontamination. Understanding the interaction between the properties of the material and the conditions of the environment in which it will be inserted is important to assess its suitability for a given application. In order to analyze the variation in static punching resistance of geosynthetics in contact with acidic effluent, which is a situation that can occur in mining waste deposits, punching tests were carried out in the CBR press, adapting a part to the equipment , on virgin samples, of 2.0 mm thick geomembranes (HDPE), protective geotextiles (with different weights) and composite systems (geotextiles+geomembranes) and the tests were repeated on samples immersed in an acidic effluent. The results demonstrated that for geotextiles, individually perforated, there was a drop in punching resistance for one of the tested samples, after contact with acid effluent, while in the other samples the resistance practically did not change, probably due to the difference in the manufacturing process and of the grammar. For the geomembrane, considering the period of exposure to the acidic effluent, there was a hardening. It was also found that the introduction of geotextiles as a protective layer provided increases in puncture resistance in relation to geomembranes tested separately in both virgin and exposed samples, with little change after contact with acidic effluent. It can be concluded that there is practically no need to use a correction factor, when dealing with the conditions here.